ANALISIS PENGARUH PEMASARAN RELASIONAL TERHADAP KEPUASAN NASABAH PT. BANK X - kezia yurischa purba; paham ginting (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT The purpose of this study are to investigate and analyze the effect of relationship marketing consisting of financial benefits, social benefits,and structural ties tocustomer satisfaction at PT. Bank X. This research was explanatory. The nature of the study was a survey. This research  used two types of data sources, namely primary data and secondary data. Primary data are obtained directly from the research object, through the results of questionnaires distributed to respondents for further processing. Secondary data are collected through journals, the Internet, and books that have relevance to the study. The population of the study were customers who have savings at PT. Bank X. The samples of the study were 98.94 take up to 100 people using Slovin formula. The analysis method was descriptive analysis and multiple linear regression analysis with a significance level of < 0.05. F-test results showed that financial benefit, social benefit and structural ties were used to estimate customer satisfaction at PT. Bank X. Significant assay results t (t-test) showed that the variable which had a positive and significant effect was social benefit variable, while the financial benefit variable and structural ties variable had a negative effect which was not significant on customer satisfaction as well. Dominant variable was the social benefit. Results determinant coefficient (R2) was 0.598, which means that relationship marketing variables had a close relationship to customer satisfaction at PT. Bank X. Adjusted R Square of 0.337 means that the value of 33.7% increase in customer satisfaction at PT. Bank X can be explained by the variable of financial benefit, social benefit and structural ties, while the remaining 66.3% can be explained by other variables which are not examined in this study. Keywords: Financial Benefit; Social Benefit; Structural Ties; and Customer Satisfaction.